2009
DOI: 10.1088/1468-6996/10/4/045006
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor effect on high-temperature oxidation behavior of Fe3Al intermetallics

Abstract: Nb) were oxidized at 950• C in dry and humid (11 vol% water) synthetic air. Thermogravimetric measurements showed that the oxidation rates of the tested intermetallics were lower in humid air than in dry air (especially for Fe 3 Al-Zr,Mo and Fe 3 Al-Zr,Mo,Nb). The addition of small amounts of Zr, Mo or Nb improved the kinetics compared with that of the undoped Fe 3 Al. Fe 3 Al showed massive spallation, whereas Fe 3 Al-Zr, Fe 3 Al-Zr,Mo and Fe 3 Al-Zr,Mo,Nb produced a flat, adherent oxide layer. The rapid tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This could be likely as a result of the crack formation either on the surface scale or within the aluminium layer which allowed access of H2O to penetrate through paths of such cracks or voids. Reaction of H2O and aluminum forms an alumina oxide with increased mass gain [24,25]. Nevertheless, the plasma spray coatings have slightly high mass gain than the hot-dip coating.…”
Section: Effect Of Aluminum Coatings On Oxidation Mechanism Of In 718mentioning
confidence: 99%
“…This could be likely as a result of the crack formation either on the surface scale or within the aluminium layer which allowed access of H2O to penetrate through paths of such cracks or voids. Reaction of H2O and aluminum forms an alumina oxide with increased mass gain [24,25]. Nevertheless, the plasma spray coatings have slightly high mass gain than the hot-dip coating.…”
Section: Effect Of Aluminum Coatings On Oxidation Mechanism Of In 718mentioning
confidence: 99%
“…Therefore, much effort has been made toward understanding the effect of water vapor on the oxidation of metallic materials. In particular, the impact of water vapor on the high-temperature oxidation behavior of alumina-forming alloys has received considerable attention because of their increasing use in emerging energy technologies such as power generation, jet engines, petrochemical processing, and solid oxide fuel cells. Most of these applications encounter a relatively high level of humidity or steam and rely on the ability of the alloys to form a protective oxide scale under the harsh service conditions. Therefore, water vapor plays a significant role in influencing the sustained use of the metallic components.…”
Section: Introductionmentioning
confidence: 99%
“…a-Al 2 O 3 transformation; whereas, Zr [8], La, Hf [14], Si [15], Pt [16,17], Y [18][19][20][21] have been reported to delay this transformation. A few investigations have dealt with the environmental effects such as water vapor [22][23][24][25] and the results are not conclusive. Chevalier et al [23] and Zhou et al [22] reported that the presence of water vapor promoted the h ?…”
Section: Introductionmentioning
confidence: 99%
“…A few investigations have dealt with the environmental effects such as water vapor [22][23][24][25] and the results are not conclusive. Chevalier et al [23] and Zhou et al [22] reported that the presence of water vapor promoted the h ? a on the Fe 3 Al intermetallic and NiAl.…”
Section: Introductionmentioning
confidence: 99%